Numerical Simulation of Cavitation - Gharraee, Behrad (My University, 2016)
As renewable energies continue to grow their share in the global energy landscape, marine resources present an inexhaustible potential to provide the ever increasing human settlements energy demands. Tidal energy conversion technologies enjoy the benefits of the accurately predictable and highly reliable resources, while promising great power to weight ratio due to the relatively small size of the equipment compared with offshore wind for instance. There are various prototypes being tested today and some proposals are employing floating structures as the platform for the energy converters, the design of which is driven by the higher kinetic energy content of the streams close to the water surface. Such concepts increase the turbines susceptibility to cavitation. There has been very little explicit research performed on the cavitation behavior of tidal turbines and this thesis attempts to establish one such study to enable and promote future investigations. The specialized hydrodynamic RANS solver ReFRESCO is used with the builtin Sauer cavitation model. Structured grids have been employed. The effectiveness of an eddy-viscosity modification method known as the Reboud correction is also subject of investigation for improving dynamic behavior of cavities. Two different turbulence models used are k-! (SST-2003) and k-p kL. A three-bladed model scale Horizontal Axis Tidal Turbine (HATT) is numerically simulated in open-water conditions in an attempt to reproduce previous EFD results from the University of Southampton, thus validating the numerical procedures in use. The simulations are performed through three stages where initially a steady solution is obtained, then the simulation becomes transient and finally the cavitation model is switched on. The results are validated against experiments via non-dimensionalized parameters for thrust and torque, which prove satisfactory. General flow shows good agreement with experimental observations and the cavity formation appears to be accurate regarding both its position and blade coverage. Interestingly a cavity is observed near the leading edge on the pressure side. The simulations fail to resolve the details near the closure line of the sheet cavity which is attributed to inadequate meshing resolution. Very little dynamic behavior of the cavity structure is observed specifically where a "horse-shoe" cavity structure had been detected during EFD, which will be subject to future work.
Keywords: Energi; Farkostteknik; Marin teknik; Havs- och vattendragsteknik; Energy; Vehicle Engineering; Marine Engineering; Ocean and River Engineering